The Relationship Between Bath Indexes and Osteoporosis in Male Patients with Axial Ankylosing Spondylitis - Hale Karapolat,; Sibel Eyigör,; Yeşim Akkoç,; Yeşim Kirazlı,; İsmail Sarı,; Servet Akar,; Nurullah Akkoç, (Archives of Rheumatology, 2008)
Objective: Osteoporosis is a common complication of patients with ankylosing spondylitis (AS). There is no avaible data for the indications of bone mineral density (BMD) measurement related to osteoporosis diagnosis at AS patients. The aim of this study is to investigate the relationship between Bath indexes and BMD in patients with AS. Materials and Methods: 45 male AS patients (mean age: 46.96±13.58 years) and 41 healthy male controls (mean age: 48.93±6.86 years) were enrolled in the study. Patients with AS were evaluated with Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Spondylitis Metrology Index (BASMI) and Bath Ankylosing spondylitis Radiology Index (BASRI). The BMD of AS and control group patients were assessed at hip (femoral neck, Ward's triangle and femur trochanter) and lumbar area. Results: We have found a significant difference at the femoral ward triangle and lomber spine BMD and T scores in favour of AS patients (p<0.05). BASMI scores were negatively correlated with femoral neck and femoral ward triangle (p<0.05). BASDAI, BASFI scores were not correlated with BMD and T scores of any measured regions. Conclusion: We found that femur ward triangle may be appropriate to evaluate bone loss in patients with AS. BASMI score is a useful tool to determine BMD in patients with AS. (Rheumatism 2008; 23: 82-6)